Analisis Hubungan Faktor Lingkungan Kerja Dengan Kesehatan dan Keselamatan Tenaga Kerja - Hilwa Irvi Adzkia; Khadijah Azzahra Lubis; Zakia Rahmah; Abdurrozzaq Hasibuan (Jaanur ElBarik Indonesia, 2026)
This study aims to analyze the relationship between work environment factors and occupational health and safety of workers. The method used is a literature review by utilizing secondary data obtained from scientific journals, books, and other relevant and reliable sources. Data collection was carried out through searching and reviewing previous studies, then analyzed descriptively by comparing, classifying, and synthesizing research findings. The results show that the work environment has a significant influence on occupational health and safety. The physical work environment, such as lighting, temperature, noise, and ventilation, directly affects workers' health conditions and the risk of workplace accidents. Meanwhile, the non-physical work environment, such as work relationships, organizational support, and safety culture, influences workers' safety behavior. These two aspects complement each other in creating a safe, healthy, and productive work environment. Therefore, comprehensive improvements in the work environment and consistent implementation of occupational health and safety management systems (OHS) are essential to reduce the risk of workplace accidents and occupational diseases